Analysis of CO2 trapping capacities and long-term migration for geological formations in the Norwegian North Sea using MRST-co2lab. (June 2015) - Møll Nilsen, Halvor; Lie, Knut-Andreas; Andersen, Odd
Abstract: MRST-co2lab is a collection of open-source computational tools for modeling large-scale and long-time migration of CO2 in conductive aquifers, combining ideas from basin modeling, computational geometry, hydrology, and reservoir simulation. Herein, we employ the methods of MRST-co2lab to study long-term CO2 storage on the scale of hundreds of megatonnes. We consider public data sets of two aquifers from the Norwegian North Sea and use geometrical methods for identifying structural traps, percolation-type methods for identifying potential spill paths, and vertical-equilibrium methods for efficient simulation of structural, residual, and solubility trapping in a thousand-year perspective. In particular, we investigate how data resolution affects estimates of storage capacity and discuss workflows for identifying good injection sites and optimizing injection strategies. Abstract : Highlights: Outline open-source tools for estimating CO2 storage potential in saline aquifers. Study how data resolution impacts estimates of structural trapping capacity. Develop plausible injection plans for storing gigatonnes of CO2 . Examples: Johansen and Utsira from the CO2 Storage Atlas of the Norwegian North Sea.